Egyptian Sculpture: Cairo and Luxor - Edna R. Russmann; David Finn (USA University of Texas Press, 1989)
This book shows the development and variations of ancient Egyptian sculptural styles over a period of almost 3,000 years with detailed commentary on each piece
The art of Egyptian sculpture -- The First Great Period -- The Classic Period -- Creation of an empire -- Revolution and aftermath -- Egypt the ancestor
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Portrait sculpture, Egyptian -- Egypt -- Cairo; Portrait sculpture, Ancient -- Egypt -- Cairo; Portrait sculpture, Egyptian -- Egypt -- Luxor; Portrait sculpture, Ancient -- Egypt -- Luxor; General